Oxidative status in bipolar disorder (BD) and its correlation with age, gender and body mass index (BMI) - Tan, Jaclyn Ai Chin; Geetha Gunasekaran; Mohd Hanafi Ahmad Damanhuri; Chan, Lai Fong; Loo, Jiann Lin; Goon, Jo Aan (Penerbit Universiti Kebangsaan Malaysia, 2019)
Bipolar disorder (BD) is a chronic psychiatric illness which molecular foundations have yet to be elucidated. Oxidative stress appears to be a promising field of study to understand the formation of this disease in molecular level. The objective was to investigate the oxidative status of BD and its association with age, gender and body mass index (BMI). A cross-sectional study was conducted in a tertiary university hospital in Cheras, Malaysia on 55 patients with BD diagnosed using Mini Neuropsychiatric Interview (MINI). Peripheral markers of oxidative stress which include superoxide dismutase (SOD), glutathione peroxidise (GPx), catalase (CAT), malondialdehyde (MDA) and DNA damage were examined in subjects with BD (n=55) and compared to healthy controls (n=28). BD patients had significantly higher concentrations of MDA compared to healthy controls (p<0.001). Concentration of MDA was significantly higher in BD patients aged 40 and above compared to those aged 39 years and below (p<0.05). The concentration of MDA did not show significant difference between male and female BD patients, likewise between patients with BMI below and above 25. The percentage of normal DNA in healthy controls was significantly higher than that of BD patients (p<0.001), while percentage of mildly and severely damaged DNA in BD patients was significantly higher than that of healthy controls (mildly damaged: p<0.001; severely damaged: p<0.001). The severity of DNA damage in the BD patients was similar when compared between age, gender and BMI. SOD activity of BD patients was found to be comparable to that of healthy subjects as well as when compared between gender and age, but was significantly lower in subjects with BMI above 25 (p<0.05). CAT activity was significantly higher in BD patients compared to controls (p<0.001), while no significant difference was found when compared between gender, age and BMI. GPx activity did not show significant difference when compared between BD and healthy controls, gender, age and BMI. Multiple linear regression analysis showed that the percentage of normal DNA increases with age in BD patients (p<0.001), while the percentage of damaged DNA decreases with age (mildly damaged: p<0.002; severely damaged: p<0.001). Percentage of normal and damaged DNA are not significantly correlated with BMI, while all antioxidative enzymes (SOD, GPx, CAT) and MDA concentration did not show significant correlation with age and BMI. In conclusion, age and BMI are associated with the oxidative status of BD patients regardless of gender.